Fish as pollution indicator with some heavy metals in the Iraqi seawater - Alhassoon , Ahmed Sh.; Ibrahim, Feryal H. (Iraqi Journal of Aquaculture, 2021)
This study is concerned with the concentrates of heavy metals (Cd , Pb and Zn ) that is found in Lisa subviridis fish, which were collected on April 2017 to September 2018, it is brought from the Iraqi seawater, samples of fish were dried by (Deep Freeze Drier), ash was estimated by furnace and then digested by Nitric acid, after digesting the samples were diluted and the above heavy metals were estimated by Flame Atomic Absorption Spectroscopy, the results shows that the upper values of estimated heavy metals concentrates (Cd, Pb and Zn) were recorded in August 2017 it was o.o48,0.062 and 0.042 mg/gm respectively, while Cd shows less recorded value in February 2018, Pb and Zn recorded less values in April and May 2018, it was 0.045 and 0.023 mg/gm respectively.